Alkanes and aliphatic carbonyl compounds in wintertime PM2.5 in Beijing, China. (1st April 2019) - Lyu, Ruihe; Shi, Zongbo; Alam, Mohammed Salim; Wu, Xuefang; Liu, Di; Vu, Tuan V.; Stark, Christopher; Xu, Ruixin; Fu, Pingqing; Feng, Yinchang; Harrison, Roy M.
Abstract: Organic aerosol is one of the dominant components of PM2.5 in megacities. In order to understand the sources and formation processes of aliphatic carbonyl compounds, the concentrations of saturated and unsaturated aliphatic hydrocarbons and carbonyl compounds were determined in the PM2.5 from an urban area of Beijing sampled in November–December 2016 and analysed using two dimensional gas chromatography coupled to time-of-flight mass spectrometry (GC x GC-TOFMS). The data were separated into non-haze and haze days (PM2.5  ≥ 75 μg m −3 ). n-Alkanes (C10 -C36 ) and n-alkenes (C12 -C26 ) were abundant in the samples during the sampling campaign regardless of non-haze and haze conditions, and the middle chain length n–alkanes (C25 –C34 ) were the most abundant. Aliphatic carbonyls, specifically n-alkanals (C8 -C29 ), n-alkan-2-ones (C8 -C31 ) and n-alkan-3-ones (C8 -C30 ) were also detected in the PM2.5 at concentrations much lower than n-alkanes. The n-alkanals were the most abundant compounds amongst the aliphatic carbonyls, accounting for 65.4% on average of the total mass of aliphatic carbonyls. For the non-haze days, it seems likely that the OH oxidation of n-alkanes was a source of carbonyl compounds, whereas vehicle exhaust makes a significant contribution to the n-alkanes and n-alkanals, but makes a much smaller contribution to the n-alkan-2-ones and n-alkan-3-ones. It appears that primary sources are likely to be a major contributor to concentrations of the high molecular weight carbonyl compounds during the haze episodes, probably deriving from coal combustion. In addition, furanones (γ-lactones) and phytone (6, 10, 14-trimethylpentadecan-2-one) were also detected in our samples and are oxidation products of hydrocarbons and a marker of biogenic input, respectively. Cooking emissions also appear to be a likely contributor to the furanones. This study provides new information on the profiles of PM2.5 -associated aliphatic hydrocarbons and carbonyl compounds, and gives insights into their sources. Differences in the concentrations and ratios of carbonyl compounds between Beijing and London are discussed. Highlights: Alkanes and carbonyls quantified in condensed phase samples. Alkanes, 2-alkanones and 3-alkanones analysed. Both primary and secondary sources of carbonyl are inferred. Both haze and non-haze conditions are sampled. Beijing and London data are compared.